Aerosol and gaseous pollutant characteristics during the heating season (winter–spring transition) in the Harbin-Changchun megalopolis, northeastern China. (July 2019) - Zhao, Hujia; Ma, Yanjun; Wang, Yaqiang; Wang, Hong; Sheng, Zhizhong; Gui, Ke; Zheng, Yu; Zhang, Xiaoye; Che, Huizheng
Abstract: Serious pollution events caused by residential heating activities occur frequently in northeastern China, and these increased particulate matter levels and gaseous pollutants could contribute to both local emissions and regional climate change. In this study, meteorological data, air trajectories and aerosol vertical distributions were used to study the pollutant sources and movement paths during the heating season (winter–spring transition) in the Harbin-Changchun megalopolis, northeastern China. Higher concentration of fine-mode particles (PM2.5 /PM10 ∼ 0.70–0.80) and the trace gas SO2 (35–45 μg m −3 ) could be seem as an indicator of the air quality in the Harbin-Changchun megalopolis during the residential heating seasons, caused by local emissions. The apparent changes of meteorological elements in the high latitude and cold regions over Northeastern China could have important effects on the pollutant formation, secondary transformation, aerosol accumulation and vertical transport over the heating season. The PM2.5 concentrations were highly associated with the SO2 and NO2 from both fossil fuel combustion and biomass burning. The obvious diurnal pollutants variation shown thermodynamic conditions could be considered one of the important environmental elements responsible for residential heating processes. The mixture effect of local emissions and aerosol convective activities were found to contribute to the aerosol extinction and air pollution in the Harbin-Changchun megalopolis. These findings could help to improve our understanding of the association between aerosol pollutants influenced by the anthropogenic activities and the aerosol regional climate effects during the heating season in northeastern China. Highlights: Residential heating contributed majority SO2 in northeastern China. Residential heating significant influenced on different aerosols diurnal variation. Emphasize the local emission and convective activity to the residential heating.